PMP® exam practice test and study guide - Levin, Ginger; Ward, J. LeRoy (CRC Press, 2015)
As in previous editions, this edition provides a clearly written rationale for each correct answer, along with a supporting reference list. To help broaden your understanding of the concepts in the answer, this edition features an expanded rationale that discusses why a particular answer is correct, some study tips to consider, and in many cases, an explanation as to why the other answers are incorrect. For each answer, the authors supply references to the appropriate pages in the PMBOK®Guide andthe specific ECO domain and task